SILENCE OF REGION, GENDER INJUSTICE IN THE SHORT STORY “A PAIR OF IMPRISONED DINAYA EYES” NI KOMANG ARIANI'S WORK - Diah Dwi Kurniyati; Juni Mahsusi (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2023)
In the practices of social life in various regions and tribes, there are still many gender injustices. Placing women as weak and do not have the same rights as men. This gender injustice is reflected in literary works, one of which is the short story A Pair of Imprisoned Dinaya Eyes by Ni Komang Ariani. This research aims to describe and explain the form of gender injustice contained in the short story A Pair of Imprisoned Dinaya Eyes by Ni Komang Ariani. The research method used in this study is a qualitative descriptive method using a feminist literary criticism approach. The data source is the short story A Pair of Imprisoned Dinaya Eyes by Ni Komang Ariani. In contrast, the data in this study are quotations from short stories, which are the problem and the purpose study. The results of the study show that there is gender inequality in the short story A Pair of Imprisoned Dinaya Eyes by Ni Komang Ariani, namely that women only take care of the household with domestic tasks, accept arranged marriages, are not allowed to work outside, and only serve their husbands, and female characters only do silent fight.